Reaction of detached fruits of chilli (Capsicum annuum L.) varieties to isolates of Colletotrichum capsici (Syd.) Butler and Bisby - Mehra, T Vanan, S K Khirbat, R (Journal of Spices and Aromatic Crops, 2005)
Investigations on the pathogenic potential of nine isolates of Colletotrichum capsici on four chilli (Capsicum annuum) varieties revealed variations in their incubation period and lesion size induced on inoculated fruits. The isolates CC-1, CC-2, CC-3, CC-4, CC-5 and CC-7 gave resistant reaction in all the four varieties. Isolate CC-9 gave susceptible reaction in all the four varieties. Isolate CC-8 induced susceptible reaction in Hisar Shakti and resistant reaction in Hisar Vijay whereas, CC-6 gave susceptible reaction in Hisar Vijay and resistant reaction in Hisar Shakti.